Analisa Kerja Belt Conveyor 5857-V Kapasitas 600 Ton/Jam - Erinofiardi, Erinofiardi (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2012)
Belt conveyor is one of famous material handling equipment on industry around the world. It can be used to transport cement, coal and others. Capacity of belt conveyor depend on wide of belt, power motor, distance of transport area, material that will be transport and velocity of belt. As a case study, PT PUSRI Palembang has belt conveyor 5857-V series 600 ton per hour capacity. The aim of this research is to find the real capacity and velocity of this belt conveyor on field and analize what factor influence if some differences come up. Based on calculation, from 37 KW power motor, real capacity of this belt conveyor is 398,33 ton per hour and its speed is 0,93 m/s. Meanwhile, to reach maximum capacity 600 ton per hour, belt conveyor needs speed 1,4 m/s by using 50 KW power motor.Keywords: Belt Conveyor, Capasity, Velocity.